Analysis Of Suffixed Words of Plywood Manufacturing Article - Jumanto Jumanto; Eugene Chung; Florence Hadi Soeroyo Oei; Misbachul Munir Al Fattah (Unipdu Jombang, 2024)
The purpose of this research to find out and analyze suffix word of the manufacturing process. The primary goal of this research is to determine how the suffixing process occurs in the manufacturing plywood. Plywood stands as a foundational building material, comprising thin wood layers or plies bonded together with adhesive. It divides into two primary categories: softwood plywood and hardwood plywood, each aligning with specific tree species. Coniferous varieties, such as firs and pines, predominantly contribute to softwood plywood, while deciduous species, including oak, poplar, maple, cherry, and larch, find prominence in hardwood plywood. Softwood plywood undergoes production by bonding multiple layers of dry softwood veneers with adhesive. Its versatile applications encompass wall siding, sheathing, roof decking, concrete formboards, floors, and containers. Within industrial classifications, it falls under Standard Industrial Classification (SIC) code 2436 and North American Industrial Classification System (NAICS) code 321212 for